Urgensi Pembaruan Hukum Dalam Menghadapi Kejahatan Yang Melibatkan Teknologi Kecerdasan Buatan AI - Muhammad Kautsar Ibrahim; Mirza hafidz; Zidane Fadilah Hanung Atmaja (Journal of Legal, Political, and Humanistic Inquiry, 2025)
The rapid development of digital technology based on artificial intelligence has given rise to new forms of crime characterized by complexity, adaptability, and a high degree of sophistication that challenge conventional criminal justice systems. This phenomenon has resulted in legal gaps and legal uncertainty, as existing regulations were not designed to comprehensively address the dynamic nature of technology-based crimes. The background of this study is rooted in the increasing challenges faced in law enforcement, the limitations of existing criminal law constructions, and the inadequate legal protection afforded to society and victims of digital crimes. This research employs a normative juridical method with a qualitative approach, utilizing library research through an examination of statutory regulations, legal doctrines, and relevant scholarly works. The findings indicate that the Indonesian criminal law system continues to face substantive, structural, and legal-cultural limitations in responding to crimes involving artificial intelligence technology. This study underscores the urgency of legal reform through the formulation of new legal norms that are adaptive and responsive, in order to address legal vacuums, strengthen legal certainty, and ensure legal protection and justice amid the increasingly rapid pace of technological development.